2017
DOI: 10.5194/isprs-archives-xlii-3-w1-7-2017
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Unmixing Based Construction of Lunar Mineral Abundance Maps

Abstract: ABSTRACT:In this study we apply a nonlinear spectral unmixing algorithm to a nearly global lunar spectral reflectance mosaic derived from hyperspectral image data acquired by the Moon Mineralogy Mapper (M 3 ) instrument. Corrections for topographic effects and for thermal emission were performed. A set of 19 laboratory-based reflectance spectra of lunar samples published by the Lunar Soil Characterization Consortium (LSCC) were used as a catalog of potential endmember spectra. For a given spectrum, the multi-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Later studies of the M 3 spectrometer onboard Chandrayaan-1 confirmed mineralogical differences between these two groups of rocks, but only in rock-forming minerals. First, lunar mare basalts show 35-50 vol.% plagioclase (Bernhardt et al, 2017;Corley et al, 2018), and lunar highland anorthosites >90 vol.% plagioclase (Cheek et al, 2013;Bernhardt et al, 2017). However, no maps show the differences between the domains of basalt mare and anorthositic highlands regarding their content of ore minerals, such as ilmenite, troilite, and others.…”
Section: Impact Cratersmentioning
confidence: 99%
See 2 more Smart Citations
“…Later studies of the M 3 spectrometer onboard Chandrayaan-1 confirmed mineralogical differences between these two groups of rocks, but only in rock-forming minerals. First, lunar mare basalts show 35-50 vol.% plagioclase (Bernhardt et al, 2017;Corley et al, 2018), and lunar highland anorthosites >90 vol.% plagioclase (Cheek et al, 2013;Bernhardt et al, 2017). However, no maps show the differences between the domains of basalt mare and anorthositic highlands regarding their content of ore minerals, such as ilmenite, troilite, and others.…”
Section: Impact Cratersmentioning
confidence: 99%
“…These areas show slightly elevated TiO 2 (1-5 wt%) and FeO T (5-15 wt%) relative to the anorthositic highlands (Lucey et al, 1998), which would imply an increased ore mineral content. The orbit of the Chandrayaan-1 mission did not allow the collection of mineralogical information from these areas by the M 3 spectrometer (Bernhardt et al, 2017). Therefore, the role of MIRORES in recognizing polar regions may be crucial.…”
Section: Goals Of the Lunar Mirores Mission And Its Justificationmentioning
confidence: 99%
See 1 more Smart Citation